Agricultural Digitalization and Strengthening Farmer Capacity through an Agricultural Website and AgriTech Workshop in Gumeng Village, Jenawi District, Karanganyar Regency - Wijayanti, Desna Ayu; Pamastutiningtyas, Terrensia Sekar; Wiyoga, Ajietama Imam; Safitri, Anggita Ghina; Aksani, Nasrin; Wulandari, Pitri; Febriana, Annisa Alfi; Irawan, Erwin; Boi, Jumiati Sulaika (Unram Journal of Community Service, 2025)
This community service activity was conducted in collaboration with the Muhammadiyah University of Karanganyar's Real Work Lecture (KKN) activities and KKN Group 13 in Gumeng Village, Jenawi District, Karanganyar Regency. The purpose of the activity is to support the development of local potential through agricultural digitalization and capacity building for farmers. The main program includes the launch of the Desa Gumeng agricultural website as a promotional and educational medium, as well as the organization of the "Agritech Evolution" workshop, which discusses balanced fertilization and environmentally friendly pest control. The implementation methods consist of website design, socialization, technical training, interactive lectures, and participatory discussions. The results of the activity show enthusiasm from approximately 30 participants, increased knowledge among farmers regarding fertilization and pest control, and the availability of a website that can be used as a marketing medium. The conclusion indicates that the synergy of digitalization and human resource capacity building is key to the success of rural agricultural development.